Accuracy of English pronoun use among Malaysian ESL 5-6 year old children and teaching implications in the Malaysian pre-school education context - Abd Samad, Arshad; Wong, Bee Eng; Arshad, Nurul Iman; Kalpany, Kaaminy (Atlantis Press, 2016)
The use of pronouns among young children is an interesting phenomenon to examine due to the psychological connections that can be made between pronouns and the developing concept of ego and self among young children. In a learning English as a Second Language (ESL) situation, however, the acquisition of pronouns may be influenced by other factors such as exposure to the forms as well as the students' first language. This largely descriptive study examines the acquisition of the English pronouns among forty 5 to 6 year old Malaysian ESL pre-schoolers. The children in the study were presented with 33 drawings to assess their familiarity with subjective, objective, possessive and reflexive English pronouns. For each drawing, the children were required to select the correct pronoun from three pronouns that were used in a sentence to describe the drawing. This study will report on accuracy rates for each pronoun, assuming that high accuracy rates indicate a more complete acquisition of the pronoun. Data obtained will be compared to acquisition sequences in the literature. Error forms will also be identified. Finally, some initial suggestions will be made on teaching English pronouns to children whose first language is not English in the context of recent teaching initiatives conducted in Malaysia.